Analysis of economic convergence of Islamic justice in selected Islamic countries - Mohammad Reza Alizadeh Emamzadeh (Journal of Economic Structures, 2020)
Justice is the most important principle in Islam and measures the extent to which decisions in Islamic countries comply with Islamic doctrine. Economic justice is a sub-domain of justice and is further subdivided to distributive justice. Distributive justice implies that improvement in economic well-being of an individual occurs to the detri-ment of another's. The present study investigates economic convergence of Islamic justice in selected Islamic countries (Albania, Bangladesh, Azerbaijan, Egypt, Guinea, Iran, Iraq, Jordan, Kazakhstan, Kosovo, Kyrgyzstan, Malaysia, Maldives, Niger, Pakistan, Senegal, Tajikistan, Turkey, Yemen And Tunisia) during 1995-2015 using beta-type con-vergence and generalized method of moment. It is argued that growth rate of income distribution in communities that suffer from bad income distribution system will move in the long run towards fair distribution. Results of absolute beta convergence indicate convergence of Gini coefficient at rate of 0.31. The Gini coefficient is significant at 1%. Moreover, results of conditional beta convergence reveal convergence of Gini coeffi-cient. Inflation rate and GDP positively affect this convergence.
Keywords: O11; C22; D33; 330; Islamic justice; Economic convergence; Islamic countries; Beta-type convergence; Generalized method of moment